The Embedded Corporation: Corporate Governance and Employment Relations in Japan and the United States - Carroll, William K. (Labour / Le Travail, 2007)
The article reviews the book, "The Embedded Corporation: Corporate Governance and Employment Relations in Japan and the United States," by Sanford M. Jacoby.
Keywords: BOOKS – Reviews; Corporate governance; EMBEDDED Corporation: Corporate Governance & Employment Relations in Japan & the United States; The (Book); JACOBY; Sanford M.; 1953-; Nonfiction